The Relationship Between Nurses’ Knowledge and the Prevention of Healthcare-Associated Infections (HAIs) Among Inpatients at Efarina Hospital Berastagi - Armeysa Br Sembiring; Sifrani Sifrani; Selly Sepriani (Sean Institute, 2026)
Healthcare Associated Infections (HAIs) are infections that patients get while undergoing treatment in a hospital or other health care facility. According to the World Health Organization (WHO) in 2022, it was reported that there were 8.9 million incidents of Healthcare Associated Infections (HAIs) in health care facilities and 1 in every 10 percent had died from nosocomial infections. This study aims to determine the relationship between nurses' knowledge and the prevention of Healthcare Associated Infections (HAIs) in the inpatient room of Hospital Efarina. The methodology of this study uses a quantitative research design with a Cross Sectional approach. Sampling used Saturated Sampling with a total of 124 respondents. The results of the study based on the Spearman p value test 0.00 <0.05 showed that there was a significant relationship between the nurses' knowledge variable and the HAIs prevention variable. Nurses are expected to be able to improve their personal knowledge and maximize their performance, especially regarding the prevention of Healthcare Associated Infections (HAIs) by participating in training and monitoring nursing staff at the Hospital Efarina.